Biological and contextual determinants of early development in marginalized Roma communities: A research protocol of the RomaREACH study - Shoshana Chovan; Daniela Fiľakovská Bobáková; Andrea Madarasová Gecková; Beáta Hubková; Gabriela Štrkolcová; Sijmen A. Reijneveld; Marlou L. A. de Kroon (BMC, 2024)
Abstract Background The period of early childhood bears significant importance from the lifespan perspective. Children from marginalized Roma communities face several risk factors that endanger their early development. Based on the gaps in available evidence, the aim of the RomaREACH research project (Research on Early Childhood in marginalized Roma communities) is, therefore, to explore the complex mechanisms influencing psychomotor development in the first 3 years of a child's life in marginalized Roma communities, and to translate and adapt instruments for measuring development and parenting in marginalized Roma communities and assess their psychometric qualities and suitability Methods The project comprises two parts. The first part is a validation study of the translated Caregiver-Reported Early Development Instrument (CREDI) and the Comprehensive Early Childhood Parenting Questionnaire (CECPAQ), tools for the assessment of early development and of parenting strategies and practices. The second part is a longitudinal cohort study, in which the relationships of risk and protective factors with development are explored. Discussion The RomaREACH project is a multicomponent study of social determinants of health and development in early childhood that can provide new evidence on the relationship of risk and protective factors with early development. Such young children from difficult-to-reach marginalized Roma communities are rarely included in research, and information about the scope and the extent of inequities in health and development in the period of early childhood is scarce. The expected results of the RomaREACH project have the potential to influence policy and practice by providing validated tools and evidence-based insights that can help mitigate the developmental risks faced by children in marginalized Roma communities and contribute to improving developmental outcomes and equity.